Internal and External Determinants of Banking Stock Performance: Evidence from the Indonesia Stock Exchange - Syahid, Aliah Muthiah; Pitriana, Ida; Lestari, Henny Setyo (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study examines the factors influencing stock performance in banking institutions listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach using panel data regression is applied to assess the impact of internal financial metrics—such as Earningss per Share (EPS), Dividend per Share (DPS), Price-to-Earningss Ratio (P/E), and Book Value per Share (BVPS)—as well as external macroeconomic variables, including inflation, Gross Domestic Product (GDP), and bank size, on Market Price per Share (MPS). The study employs the random-effect model, along with statistical tests such as Chow, Hausman, and Lagrange Multiplier, to determine the most suitable regression model. The results reveal that EPS, BVPS, and bank size have significant positive impacts on MPS, indicating that higher profitability, strong intrinsic equity value, and larger institutional size are associated with better stock performance. In contrast, DPS, P/E, inflation, and GDP show no significant influence, suggesting that investors in the banking sector focus more on other aspects, such as EPS, BVPS, and bank size rather than the amount of dividends distributed, share price compared to profitability, inflation, and GDP.